PENGARUH LITERASI KEUANGAN DAN KOMPETENSI KEWIRAUSAHAAN TERHADAP KEMAJUAN USAHA MELALUI INOVASI PRODUK PADA PELAKU UMKM NASABAH KAMPUNG MADANI PT PERMODALAN NASIONAL MADANI CABANG BANDUNG - Irani Fita Rahayu; Eduardus Suharto (Jurnal Ekonomi dan Bisnis, 2026)
This study aims to examine the effect of financial literacy and entrepreneurial competence on business progress through the mediation of product innovation among micro-entrepreneurs. The research object comprises 80 active customers of Kampung Madani Areng PT Permodalan Nasional Madani Bandung Branch, operating in the agricultural and livestock sectors in Lembang District, West Bandung Regency. A quantitative approach was employed using a census method and Structural Equation Modeling-Partial Least Square (SEM-PLS) analysis with SmartPLS version 4. Business progress was measured through actual growth data from 2024 to 2025, while other variables were measured using Likert scales. The findings indicate that financial literacy and entrepreneurial competence positively and significantly affect product innovation, and product innovation positively and significantly affects business progress, while neither variable proved to have a significant direct effect on business progress. Product innovation was found to partially mediate the effects of financial literacy (VAF = 76.19%) and entrepreneurial competence (VAF = 31.34%) on business progress, confirming that intangible resources require a concrete transformation mechanism to generate measurable business growth.